Facile access to functional polyacrylates with dual stimuli response and tunable surface hydrophobicity - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Mane, Shivshankar R.; Banerjee, Sanjib (Polymer Chemistry, 2021)
Magnetically separable and reusable Ni-Co alloy nanoparticles were employed to achieve ambient temperature reversible deactivation radical polymerization (RDRP) of methyl acrylate (MA), for the first time, yielding well-defined PMA (at least up to 124 500 g mol(-1)) with a low dispersity (D <= 1.20). The controlled polymerization character of RDRP of MA was confirmed from the linear semilogarithmic plot exhibiting pseudo first order kinetics, a linear increase of the molecular weight of the polymer with monomer conversion maintaining low D and the synthesis of PMAs of varying molecular weights from 2200 to 124 500 g mol(-1) with low D. In addition, linear PMA-Br was used as a macroinitiator for the synthesis of several well-defined PMA-b-poly(M) block copolymers (where ``M'' stands for (2-dimethylamino)ethyl methacrylate (DMAEMA), tert-butyl methylacrylate (TBMA) and 2,2,3,3,4,4,5,5-octafluoropentyl acrylate (OFPA)), with acceptable Ds (<= 1.24), demonstrating the high chain-end fidelity of the macroinitiator. The synthesized PMA-b-PDMAEMA demonstrated dual pH- and thermo-responsive properties. Upon hydrolysis, the synthesized PMA-b-PTBMA leads to the formation of unprecedented carboxylic acid-functionalized PMA derivatives. PMA-b-POFPA copolymers with varying OFPA mol% in the copolymer led to polymers with tunable surface hydrophobicity, as revealed by the water contact angle measurements.

L-Histidine-derived smart antifouling biohybrid with multistimuli responsivity - Mohammad, Sk Arif; Dolui, Subrata; Kumar, Devendra; Mane, Shivshankar R.; Banerjee, Sanjib (Biomacromolecules, 2021)
A novel dual pH/thermoresponsive amphiphilic poly(histidine methacrylamide)-block-hydroxyl-terminated polybutadiene-block-poly(histidine methacrylamide) (PHisMAM-b-PB-b-PHisMAM) triblock copolymer biohybrid, composed of hydrophobic PB and ampholytic PHisMAM segments, is developed via direct switching from living anionic polymerization to recyclable nanoparticle catalyst-mediated reversible-deactivation radical polymerization (RDRP). The transformation involved in situ postpolymerization modification of living polybutadiene-based carbanionic species, end-capped with ethylene oxide, into dihydroxyl-terminated polybutadiene and a subsequent reaction with 2-bromo-2-methylpropionyl bromide resulting in a telechelic ATRP macroinitiator (Br-PB-Br). Br-PB-Br was used to mediate RDRP of an L-histidine-derived monomer, HisMAM, yielding a series of PHisMAM-b-PB-b-PHisMAM triblock copolymers. The copolymer's stimuli response was assessed against pH and temperature changes. The copolymer is capable of switching among its zwitterionic, anionic, and cationic forms and exhibited unique antifouling properties in its zwitterionic form. These novel triblock copolymers are expected to be show promising potential in biomedical applications.

Amino acid-derived ABCBA-type antifouling biohybrid with multi-stimuli responsivity and contaminant removal capability - Kumar, Devendra; Mohammad, Sk Arif; Kumar, Anand; Mane, Shivshankar R.; Banerjee, Sanjib (Polymer Chemistry, 2022)
Multi-stimuli (pH/thermo/redox)-responsive amphiphilic poly(cysteine methacrylamide)-block-poly(2-(dimethylamino)ethyl methacrylate)-block-polybutadiene-block-poly(2-(dimethylamino)ethyl methacrylate)-block-poly(cysteine methacrylamide) (PCysMAM-b-PDMAEMA-b-PB-b-PDMAEMA-b-PCysMAM) pentablock copolymer biohybrids, based on hydrophobic PB, ampholytic redox responsive PCysMAM and dual (pH and temperature) stimuli responsive PDMAEMA segments, are synthesized via a four-step synthesis protocol. The synthesis protocol involves: (1) in situ post polymerization modification of living polybutadiene-based carbanionic species to prepare hydroxyl terminated polybutadiene (HTPB); (2) introduction of an initiating functionality (capable of acting as an ATRP initiator) to HTPB, yielding a telechelic ATRP macroinitiator (Br-PB-Br); (3) recyclable alloy-mediated successive RDRP of DMAEMA and CysMAM, yielding a series of PCysMAM-b-PDMAEMA-b-PB-b-PDMAEMA-b-PCysMAM (A-B-C-B-A) pentablock copolymers with various chain lengths; and (4) conversion of the PDMAEMA block to poly(quaternary ammonium) (PQA) via quaternization. The stimuli responsiveness of the copolymer is investigated against changes in pH, temperature and redox. The pentablock copolymer self-assembles into spherical nanospheres, can switch between its monocationic, zwitterionic and monoanionic charged states, exhibits antifouling behaviour and is capable of removing ionic contaminants from water. These pentablock copolymers may emerge as a promising material for emerging applications.